Brug Over den Brantas te Kediri sebagai Penghubung Wilayah di Kediri Tahun 1855-1912 - Niswaturrozanah, Nabila (UIN Sunan Gunung Djati Bandung, 2024)
This research discusses the Brug Over den Brantas te Kediri in 1855-1912. People refer to this bridge as the Old Bridge which is a link to the Kediri region. The Old Bridge became one of the facilities built by the Dutch for smooth transportation and provided benefits for the people of the Kediri region because it could facilitate transportation over the river. This research describes several things related to the Old Bridge, first, how the history of the Old Bridge. Second, how the Old Bridge acts as a connector of the Kediri region. Third, how the influence of the Old Bridge on the economic development and progress of the Kediri region. This research uses historical research methods, namely heuristics, verification, interpretation, and historiography. The results of this study are: First, the Old Bridge was built by the Dutch East Indies government as grootepostweg. Second, the Old Bridge plays an important role as a link between two important areas in Kediri, because of the Old Bridge the relationship between the west and east of the river became better. Third, the Old Bridge had a good influence on the economic growth and development of the Kediri region.